2013
DOI: 10.5432/jjpehss.12031
|View full text |Cite
|
Sign up to set email alerts
|

Trends in body mass index and physical fitness of Japanese university students over 26 years and the association between these parameters

Abstract: : Trends in body mass index and physicalˆtness of Japanese university students over 26 years and the association between these parameters. Japan J. Phys. Educ. Hlth. Sport Sci. 58: 181 194, June, 2013 AbstractThe purpose of this study was to examine trends in the body mass index (BMI) and physical tness of Japanese university students over a period of 26 years and the association between these parameters. We retrospectively collected data on 17,514 students aged 18 19 years attending a university in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Chinese research on physical health among students in 2014 showed that the physical fitness of undergraduates continues to decline and being overweight or obese in college students is increasingly common, which has also been found in previous studies [1][2][3]. Likewise, the situation of physical fitness in foreign college students is also not optimistic [4][5][6]. Related with the future of countries, the increasing incidence of overweight and obesity and decreasing physical fitness of undergraduates have already been serious urgent problems current societies face.…”
Section: Introductionmentioning
confidence: 59%
“…Chinese research on physical health among students in 2014 showed that the physical fitness of undergraduates continues to decline and being overweight or obese in college students is increasingly common, which has also been found in previous studies [1][2][3]. Likewise, the situation of physical fitness in foreign college students is also not optimistic [4][5][6]. Related with the future of countries, the increasing incidence of overweight and obesity and decreasing physical fitness of undergraduates have already been serious urgent problems current societies face.…”
Section: Introductionmentioning
confidence: 59%
“…Shimojo et al [16] investigated the annual changes in physique, muscle strength, and motor ability in university students over 26 years, from the peak of physical strength in 1984 until 2010 and, although there were some missing years, the trends over time in physical strength by body type classification based on BMI. However,, statistical stability is not obtained in category analysis using data for a single university, and limitations to the study must be recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The Ministry of Health, Labour and Welfare recommends that moderate-vigorous physical activity, including lifestyle activities, be performed for 60 minutes a day to maintain good health and prevent illness (Ministry of Health, Labour and Welfare, 2013). However, there are reports stating that the physical activity of Japanese people is on a declining trend and the physical fitness of young university students is generally declining (Shimojyo et al, 2013), and the decline in physical activity in women is conspicuous (Ministry of Health, Labour and Welfare, 2019). The habits of pre-adulthood exercises have an impact on the exercise habits in adulthood (Suzuki, 2009).…”
Section: Introductionmentioning
confidence: 99%